Caregiver Stress in Dealing with Traumatic Brain Injury Family Members - Paramjit Singh Jamir Singh; Azlinda Azman; Rajwani Md. Zain (Asian Social Work Journal, 2022)
Traumatic brain injury (TBI) is sudden damage to the brain caused by a jolt or blow to the head. The common causes of TBI are due to falls, sports injuries, and car or motorcycle crashes. TBI can be classified into several types, ranges from a mild concussion to severe permanent brain damage. Nevertheless, the impacts of TBI are quite devastating not only to the patient but also on the family. It may last for several years, hence the affected patient definitely requires ongoing care which is normally provided by informal caregivers, such as spouses, parents, or other family members. In addition, TBI can cause drastic changes to the life of the family members. The caregiver’s stresses including psychological problems, family burdens, changes in behavior and changes in social roles will be discussed critically in this article. Based on the literature, many caregivers lack good coping strategies in dealing with their stress. More well-designed interventions is an absolute necessity among TBI family caregivers to lessen the stress and improve their social well-being and functioning.